Feasibility of Network-Based, Online Endovascular Simulator Training in Real Time: Results from a Pilot Study - Feyen, Ludger; Minko, Peter; Franke, Nina; Völker, Martin; Haage, Patrick; Paprottka, Philipp; Nadjiri, Jonathan; Katoh, Marcus (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2023)
Purpose To test the feasibility of an online, simulator-based comprehensive interventional radiology (IR) training curriculum in times of COVID-19-induced travel restrictions.Materials and Methods A network of six VIST simulators (Mentice, Gothenburg, Sweden) was installed in six geographically different radiology departments. Two courses with six sessions each took place. 43 participants were recruited on a voluntary basis among local residents. The training sessions were conducted in real time with interconnected simulation devices and were led by experts in the field of IR on a rotational basis. The participants attitude toward various topics was quantified before and after training on a seven-point Likert scale (1 = “not at all”, 7 = “to the highest degree”). In addition, post-course surveys were conducted.Results The courses led to an improvement for all items compared with baseline: interest in IR (pre: 5.5, post: 6.1), knowledge of endovascular procedures (pre: 4.1, post: 4.6), likelihood of choosing IR as a subspecialty (pre: 5.7, post: 5.9). Experience with endovascular procedures (pre: 3.7, post: 4.6) improved significantly (p = 0.016). In the post-course surveys high satisfaction rates with the pedagogical approach (mean 6), the teaching content (mean 6.4), and the duration and frequency of the course (mean 6.1) were observed.Conclusion The implementation of a simultaneous endovascular online training curriculum in different geographic locations is feasible. The curriculum has the potential to meet the demand for training in IR in times of COVID-19-associated travel restrictions and can complement future training in the context of radiologic congresses.Key Points:
Keywords: interventional procedures; simulation; education; endovascular training; angiography